Effect of Nickel Precursor on the Catalytic Performance of Graphene Aerogel‐Supported Nickel Nanoparticles for the Production of COx‐free Hydrogen by Ammonia Decomposition. Issue 3 (12th January 2022) - Kocer, Tolga; Saraç-Öztuna, F. Eylül; Kurtoğlu-Öztulum, Samira F.; Unal, Ugur; Uzun, Alper
Abstract : Graphene aerogel (GA), a promising porous material with high specific surface area and electrical conductivity, is utilized to disperse nickel nanoparticles to reach high catalytic activity in CO x ‐free hydrogen production from ammonia. Ni(NO3 )2 ·6H2 O and Ni (II) acetylacetonate (Ni(acac)2 ) were considered as metal precursors and the pH of the impregnation solution was varied to investigate the effects on the catalytic properties of the GA‐supported nickel catalysts. Data showed that the best dispersion and homogeneity, as well as the catalytic performance, is achieved with Ni(acac)2 . An average Ni nanoparticle size of 13.6 ± 4.3 nm was obtained on the GA‐supported catalyst prepared by using Ni(acac)2 dissolved in an impregnation solution with a pH of 10.2. This catalyst with a Ni loading of 11.1 wt% provided an ammonia conversion of 70.2% at a space velocity of 30 000 mL NH3 gcat −1  h −1 and 600 °C corresponding to a hydrogen production rate of 21.5 mmol H2 gcat −1  min −1 . Data illustrated that the difference between the point of zero charge of the support and the pH of the impregnation solution set by the type of the Ni precursor is a major parameter controlling the metal dispersion and the consequent catalytic activity. Abstract : The pH of the impregnation solution used to prepare graphene aerogel (GA)‐supported Ni catalysts influences the interaction between GA and Ni nanoparticles, which tunes the Ni dispersion, and thus catalytic performance. Results show that the best Ni dispersion and ammonia decomposition performance were obtained on the GA‐supported catalyst prepared by using Ni (II) acetylacetonate.